PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 005 RANTAU PANJANG KIRI - Aisah, Siti; Daud, Damanhuri; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the low student learning outcomes. It was seen from the percentage of test scores of students who reach KKM (Complete Minimum Criteria) in class V Elementary School 005 Rantau Panjang Kiri is 44.00% of the 25 students with an average value was 68.00. The school is defined KKM 70. This research aims to improve science learning outcomes of students through learning model Problem Based on Elementary School fifth grade students Rantau Panjang 005 Left school year 2014/2015. The research was conducted in April 2015 the number of 25 students, 12 male students and 13 female students number of design research is classroom action research parameter measured is the result of the activity of the teacher and student learning activities of students. Based on the results of data analysis from the discussion of the value of the average scores of students before the application of the basic learning model based problem is 68.00, then rose to 74.40 in the first cycle and increased return on the second cycle into 81.40. So the percentage increase in base score improvement of 9.41% for the first cycle and the percentage increase in base score the second cycle to 19.70%. Mastery learning students in the first cycle showed that 80.00% reaching KKM predetermined by category classical completeness is not completed and the second cycle increased to 92.00% with the category of classical completeness completed. Results of the first cycle of observation at the first meeting showed the activity of teachers (62.50%) and at the second meeting (72.50%). In Cycle II observation of teacher activity increased in the first meeting (77.50%) and the second meeting (85.00%). For the first cycle of student activity at the first meeting (65.00%) and at the second meeting (72.50%). Student activity at the first meeting of the second cycle (80.00%) increased in the second meeting (85.00%). Based on the conclusion that the application of learning models based problems can increase student learning outcomes Class V SDN 005 Rantau Panjang Kiri acceptable. Keyword: Model Problem Based Instruction, Science Learning Result